2010
DOI: 10.1103/physrevd.81.035019
|View full text |Cite
|
Sign up to set email alerts
|

Sneutrino dark matter: Symmetry protection and cosmic ray anomalies

Abstract: We present an R-parity conserving model of sneutrino dark matter within a Higgsphilic Uð1Þ 0 extension of the minimal supersymmetric standard model. In this theory, the parameter and light Dirac neutrino masses are generated naturally upon the breaking of the Uð1Þ 0 gauge symmetry. One of the right-handed sneutrinos is the lightest supersymmetric particle. The leptonic and hadronic decays of another sneutrino, taken to be the next-to-lightest superpartner, allow for a natural fit to the recent results reported… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 115 publications
(142 reference statements)
0
29
0
Order By: Relevance
“…SUSY models of sterile neutrinos can be naturally realised in U(1) ′ extended models [472]: sterile neutrino masses of O(1 eV) and mixings among the active and sterile neutrinos can then be obtained via the high-dimensional operators, generated by integrating out the heavy fields. In U(1) ′ extended models where the vev s generates Dirac neutrino masses through a dimension-4 term in the superpotential, the decays of the LSP and NLSP (the two lightest sneutrinos) could explain the PAMELA anomaly [475].…”
Section: U(1) ′ -Extensions Of the Nmssmmentioning
confidence: 99%
“…SUSY models of sterile neutrinos can be naturally realised in U(1) ′ extended models [472]: sterile neutrino masses of O(1 eV) and mixings among the active and sterile neutrinos can then be obtained via the high-dimensional operators, generated by integrating out the heavy fields. In U(1) ′ extended models where the vev s generates Dirac neutrino masses through a dimension-4 term in the superpotential, the decays of the LSP and NLSP (the two lightest sneutrinos) could explain the PAMELA anomaly [475].…”
Section: U(1) ′ -Extensions Of the Nmssmmentioning
confidence: 99%
“…Older analyses are available for MSSM [23], though the production, decay and identification of charginos and neutralinos have received some attention very recently, given the failure to find squarks and gluinos at the LHC [24]. While in a previous work [25], we showed that in a minimal U (1) ′ model (with one extra singlet boson), choosing the right-handed sneutrino as the LSP could be consistent with the excess positron observed in satellite experiments, for the purpose of this work, in the secluded sector U(1) ′ , we take the lightest neutralino consistently to be the lightest supersymmetric particle (LSP) and therefore a dark matter (DM) candidate.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work [8], we showed that a minimal U(1) ′ model (one extra singlet boson) could be consistent with the excess positron observed in satellite experiments, choosing on of the right-handed sneutrinos as the LSP. However, for the purpose of this work (dependent on parameter space chosen to compare our results with those of MSSM), the secluded sector U(1)…”
Section: Introductionmentioning
confidence: 85%
“…′ model with one singlet and right handed sneutrinos [8] can explain the excess positron flux observed by various satellite experiments. However, this requires a rather special mass spectrum.…”
Section: Discussionmentioning
confidence: 99%